Refleksi Kesesuaian Kompetensi Lulusan Prodi S-1 Pendidikan Bahasa dan Sastra Indonesia di Universitas Negeri Surabaya - Septiana, Hespi; Shelya Chabibah; Titik Indarti; Yuniseffendri (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2026)
This study aims to reflect on the suitability of the competencies of graduates of the S-1 Indonesian Language and Literature Education Study Program, Surabaya State University, in 2019-2021 with the demands of the world of work. The reflection is oriented to find gaps between the competencies of graduates and the demands of the world of work in reality so that efforts can be made to improve the curriculum, improve the quality of teachers, and adjust and improve the learning system. This research is descriptive and has a quantitative approach. Data collection was carried out by collecting the results of the alumni tracer study survey in 2019-2021. The data were analyzed with descriptive statistics to reveal the dynamics of the suitability of graduate competencies from 2019-2021. This research produces an informative description of alumni employment, the closeness of the field of study to alumni employment, sources of information for finding job vacancies, job selection considerations, and assessment of the effectiveness of learning methods.